An investigation of the relationaship between taxi company safety climate and safety performance of taxi drivers in Iloilo City. - Dioco, Jasper C. (2017.)
The study investigated the relationship of taxi company safety climate and drivers? safety motivation and knowledge on taxi drivers? safety performance. The participants, a total of 84 taxi drivers from three taxi companies, were asked to fill out the Transportation Companies? Climate Scale (TCCS), Safety Motivation and Knowledge Scale, Occupational Safety Motivation Questionnaire, Global Safety Climate Scale and a background information form. Results of correlational analyses revealed that safety climate is not related to safety performance. It was also found that both the safety motivation and safety knowledge were significantly correlated to safety performance. Hierarchical regression analyses also showed that safety motivation predicts the most variance in safety participation. The results have both theoretical and practical implications by confirming the proximity of relationship of the variables to organizational outcomes and informing future safety interventions for the promotion of safe organizational behavior.
Thesis (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Taxi drivers -- Iloilo City; Safety Performance -- Taxi Drivers; Safety Climate -- Taxi Drivers